ASSOCIATION OF COMBINED GENOTYPE OF POLYMORPHIC CYTOKINE GENES SITES, ENDOTHELIAL GROWTH FACTOR AND METALLOPROTEASES WITH MYOCARDIAL INFARCTION DEVELOPMENT IN MEN - V. I. Konenkov; V. F. Prokofiev; A. V. Shevchenko; E. A. Pokushalov; A. M. Karaskov (Российский кардиологический журнал)
Aim. To study the relationship of combined genetic signs that include the genes from the cytokine, growth factors and matrix metalloproteases families with proinflammatory and proangiogenic activity in patients with myocardial infarction (MI).Material and methods. Totally 363 europeoid men studied at the age of 33 to 84 y.o. (mean age 55,3±0,5 y.o.), including 268 after MI and 95 healthy individuals. The mononucleotide polymorphism of promotor region of cytokine genes (TNF-308, TNF-238, TNF-863, IL1B-511, IL1B-31, IL4-590, IL6-174, IL10-592, IL10-1082), endothelial growth factor (VEGF+936, VEGF-2578) and matrix metalloproteases (MMP2-1306, MMP3-1171, MMP9-1562) studied. Genotyping was performed by the restrict analysis method of amplification products (RFLP).Results. In general 30 genetic combination found, associated with predisposition to MI, and 37 combinations, associated with endurance to it with the level of statistical significance at p<0,005. Combinations, that were actively associated with the MI development, included VEGF, containing in their homo- and heterozygous variants allele C, associated with high level of endothelial growth factor production. Among gene polymorphisms, negatively associated with MI, that differs from positively associated genotype combinations, the MMP genotypes predominate. Among the latter the homozygous CC gene MMP9 in polymorphic position C1562T, that provides high level of this enzyme synthesis.Conclusion. High specificity of gene groups in MI with proinflammatory and proangiogenic activity makes possible to use these complex signs as personified biological markers for MI prognosis in group of patients with coronary disorders and to findout the subjects required preventive activities, that decrease the risk of the disease.